Molecular Complexity and Diversity from Aromatics. The Chemistry of Spiro[cyclohexa-2,4-dienone-6,2′-oxiranes] and Their Congeners: Cycloaddition and Beyond - Singh, Vishwakarma (Synlett, 2013)
The efficient generation of complex molecular architectures from simple precursors is one of the most important aspects in the design and development of synthetic methodologies. The chemistry of reactive species generated by the oxidative dearomatization of phenols, such as o-quinone acetals, 6-acetoxycyclohexa-2,4-dienones, and their congeners, has stimulated widespread interest among organic chemists, and the use of such reactive species has emerged as a powerful method for the efficient synthesis of complex molecules. Our approach to create molecular complexity and diversity involves the oxidative dearomatization of 2-(hydroxymethyl)phenols to give spiro[cyclohexa-2,4-dienone-6,2′-oxiranes], followed by cycloaddition and transformation of the resulting adducts in the ground and excited states. In this account, we describe the evolution of the methodology and its application which has led to the development of novel and efficient routes to a diverse array of complex molecular architectures from simple aromatics.1 Introduction2 Cycloaddition of Cyclohexa-2,4-dienones of Types 3 and 4 and Manipulation of the Adducts in the Ground and Excited States2.1 Cycloaddition of Cyclohexa-2,4-dienones of Types 3 and 4: An Efficient Route to Functionalized and Appended Bicyclo[2.2.2]octanes2.1.1 Cycloaddition of Cyclohexa-2,4-dienones of Types 3 and 4 with Electron-Deficient π-Partners2.1.2 Cycloaddition of Cyclohexadienones of Type 4 with Vinyl Ethers and Vinyl Acetate2.1.3 Cycloaddition of Cyclohexadienones of Types 3 and 4 with Acyclic 1,3-Dienes: Direct Entry to Bicyclo[2.2.2]octenones Having an endo-Vinyl Group2.2 Manipulation of the Oxirane Moiety or the Chloromethyl and Hydroxy Groups in the Adducts: Synthesis of Embellished Bicyclo[2.2.2]octanes2.3 3,3-Sigmatropic Shift in Bicyclo[2.2.2]octanes: A General Stereoselective Route to Functionalized cis-Decalin Derivatives2.4 Sigmatropic Rearrangements of β,γ-Enones in Excited States: Stereoselective Routes to Bicyclo[3.3.0]- and Bicyclo[4.2.0]octanes and Tricyclic Compounds3 Synthetic Applications3.1 Synthesis of Hirsutic Acid C and the Framework of Pupukeananes from a Common Precursor3.2 Chemistry of Fused Spiro[cyclohexa-2,4-dienone-6,2′-oxiranes] and Their Adducts: Synthesis of Propellanes and Steroid–Polyquinane Hybrids3.2.1 A General Route to [3.3.3]- and [4.3.3]Propellanes3.2.2 Synthesis of Steroid–Polyquinane Hybrids3.3 Synthesis of Tri- and Tetracyclic Networks of Atisane Diterpenoids3.3.1 Synthesis of Tricyclo[6.2.2.01,6]dodecanes and Their Homologues3.3.2 Synthesis of the Tetracyclic Network of Atisane Diterpenoids: An Interesting Manifestation of Subtle Control by a Remote Functional Group3.4 Intramolecular Cycloaddition of Cyclohexa-2,4-dienones: Synthesis of Platencin4 Summary and Outlook
Keywords: oxidative dearomatizations; cyclohexa-2,4-dienones; cycloadditions; bicyclo[2.2.2]octanes; photochemistry